2015
DOI: 10.1007/s00125-015-3760-z
|View full text |Cite
|
Sign up to set email alerts
|

A high-risk phenotype associates with reduced improvement in glycaemia during a lifestyle intervention in prediabetes

Abstract: Aims/hypothesis Lack of reversal of prediabetes (impaired glucose tolerance and/or impaired fasting glucose) to normal glucose regulation (NGR) during a lifestyle intervention is strongly associated with a higher incidence of diabetes later in life. In the Tübingen Lifestyle Intervention Program (TULIP) we hypothesised that an at-risk phenotype may exist at baseline that associates with this nonresponse to the intervention. Methods A total of 120 participants of TULIP with prediabetes at baseline were studied.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
1
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 39 publications
4
41
1
5
Order By: Relevance
“…For the design, development and practice of improved and more successful lifestyle intervention programmes, it is important to reveal risk factors for short-and long-term success of a lifestyle intervention. Regarding short-term success, we previously found that the phenotype encompassing participants with a low disposition index or insulin-resistant NAFLD have a high risk for acute glycaemic non-response to lifestyle intervention [15]. The present study now demonstrates that such a phenotype is also associated with long-term non-response and extends the phenotype to impaired proinsulin conversion.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…For the design, development and practice of improved and more successful lifestyle intervention programmes, it is important to reveal risk factors for short-and long-term success of a lifestyle intervention. Regarding short-term success, we previously found that the phenotype encompassing participants with a low disposition index or insulin-resistant NAFLD have a high risk for acute glycaemic non-response to lifestyle intervention [15]. The present study now demonstrates that such a phenotype is also associated with long-term non-response and extends the phenotype to impaired proinsulin conversion.…”
Section: Discussionsupporting
confidence: 68%
“…One factor might be the decrease in insulin sensitivity that is correlated with the amount of weight loss [19]. However, the correlation of weight loss and glycaemia is not very strong [15]. Paradoxically, in the US DPPOS a stronger weight loss even adversely affected diabetes risk, independent of the previous intervention [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Caucasians from the southern part of Germany participated in the Tübingen Lifestyle Intervention Program (TULIP)1617. Individuals were included into the study when they fulfilled at least one of the following criteria: a family history of type 2 diabetes, a BMI >27 kg/m 2 , previous diagnosis of impaired glucose tolerance or gestational diabetes.…”
Section: Methodsmentioning
confidence: 99%
“…This is exemplified by a recent analysis of data from the TULIP study, demonstrating that stratification of subjects with prediabetes by phenotype (including impaired insulin secretion, insulin resistance, and non-alcoholic fatty liver) at baseline predicts the effectiveness of a lifestyle intervention to achieve normal glucose homeostasis. More specific, the latter study demonstrated that a high-risk phenotype at baseline was associated with reduced improvement in glycemia following lifestyle intervention [60]. …”
Section: Metabolically Healthy Obesity: a Misleading Concept?mentioning
confidence: 99%